Penurunan Tekanan Darah Wanita Hamil dengan Perendaman Kaki Air Hangat - Nadia Aryani; Nofri Zayani (Jurnal Sehat Mandiri, 2020)
Hydrotherapy non-pharmacological treatment for hypertension during pregnancy needs to be developed because it is safe for mother and fetus. Hydrotherapy soaking feet using warm water can increase vasodilation and increase blood flow, thereby lowering blood pressure. The purpose of this study was to determine the effectiveness of foot soaking with warm water to reduce hypertension in pregnant women. The pre-experimental research design was one group pretest posttest, which measured blood pressure before and after warm water therapy was given to pregnant women with hypertension for three days. The research sample was selected using purposive sampling method and the number was 15 people. Data analysis was performed by using paired sample T-Test. Results: Giving hydrotherapy soaking feet using warm water reduced systolic and diastolic blood pressure in pregnant women (p = 0.000 <0.05). Hydrotherapy is effective in reducing systolic blood pressure by 13-16 mmHg and diastolic by 8-9 mmHg. Conclusion: Hydrotherapy soaking feet using warm water is effective in reducing hypertension of pregnant women who go to dr. Jerry Kp. Kulon waterfall. Suggestion: Apply the foot soaking method with warm water as a non-pharmacological method of hypertension in pregnant women.